Evolution of the Development of Core Competencies in Pharmaceutical Medicine and Their Potential Use in Education and Training - Peter D. Stonier; Honorio Silva; Alan Boyd; Domenico Criscuolo; Felicity J. Gabbay; Kyoko Imamura; Gustavo Kesselring; Sandor Kerpel-Fronius; Heinrich Klech; Ingrid Klingmann (Frontiers Media S.A., 2020)
The evolution of postgraduate vocational education and training in pharmaceutical medicine is described alongside the growth of this scientific-medical discipline and profession for the development of new medicines. Over the past 50 years, whilst the training of competent professionals for their work has been paramount, this has paralleled the need to engage with the rapid and complex changes in R&D technologies, patient and healthcare system needs, and the ethical and regulatory obligations applied to the development of medicines throughout their lifecycle. The move from unstructured training to formal programs with syllabus, curricula and assessments for certification, has been accompanied by educational changes to outcomes-based, learner-centered, competency-based programs. The evolution of education and training along with the development of the set of 57 core competencies for professional practitioners in pharmaceutical medicine are described within the competence framework of seven domains: discovery of medicines and early development; clinical development and clinical trials; medicines regulation; drug safety and surveillance; ethics and subject protection; healthcare marketplace; communication and management. The application of the core competencies in a harmonized, international platform of education and training in medicines development at the undergraduate, postgraduate and continuing professional development levels would invigorate the potential for having a competent workforce with the intent to provide faster access to better and appropriate medicines for patients worldwide.